Biochar of post-extraction coffee bean ground as materials for ammonium adsorption - Hoai Linh, Nguyen; Kim Chi, Ngo; Le Minh, Tran; Ngoc Phuong, Dang; Xuan Tung, Nguyen; Thuy Tien, Do; Hong Minh, Pham Thi (Vietnam Journal of Science and Technology, 2024)
The presence of ammonium in drinking water poses a significant global challenge, demanding strategies that safeguard both public health and the environment. By exploring the potential of coffee processing byproducts, this research seeks to contribute to the development of sustainable and efficient solutions for mitigating ammonium contamination in groundwater. This study investigates the adsorption potential of AC-GCB biochar, obtained by pyrolyzing green coffee extracted bioactive compounds at 400 ºC, for ammonium removal from groundwater. The biochar's microstructure was characterized using scanning electron microscope (SEM), Fourier-transform infrared spectroscopy (FTIR), and Energy dispersive spectrometry (EDS) Mapping. Optimal adsorption conditions were observed at an initial pH range of 4 to 8, an initial NH4+ concentration of ≤ 25 mg.L-1, and a biochar dose of 10 g.L-1. The ammonium adsorption of AC-GCB was consistent with both Langmuir and Freundlich's adsorption theories (R2 > 0.92). The AC-GCB biochar obtained the maximum adsorption capacity Qm of 14.48 mg.g-1, higher than the control BC-GCB biochar that pyrolysised without bioactive compound extraction, i.e. with Qm of 5.41 mg.g-1.